A Meta-Regression Analysis to Evaluate the Influence of Branched-Chain Amino Acids in Lactation Diets on Sow and Litter Growth Performance - Julia P. Holen; Mike D. Tokach; Jason C. Woodworth; Joel M DeRouchey; Jordan T. Gebhardt; Evan C. Titgemeyer; Robert D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2021)
A meta-regression analysis was conducted to evaluate the effects of branched-chain amino acids (BCAA) in lactating sow diets on litter growth performance, sow body weight change, and sow feed intake. Thirty-four publications that represented 43 trials with similar dietary Lys, but varying BCAA were used to develop a database that contained 167 observations. Diets from each trial were reformulated using NRC nutrient loading values in an Excel-based spreadsheet. Significant predictor variables within three optimum equations developed for litter ADG included the count of weaned pigs per litter, NE, SID Lys, CP, sow ADFI, Val:Lys, Ile:Lys, and Leu:Val. The equations suggest that the number of pigs weaned per litter and increasing NE, ADFI, SID Lys, and CP for sows are large, positive drivers for litter growth. Among the BCAA, the models for litter ADG indicate a positive influence of increasing Ile:Lys and Val:Lys and reducing Leu:Val on litter growth. For sow BW change, significant predictor variables within two competing models included litter size at 24 h, sow ADFI, Leu:Lys, and Ile+Val:Leu. The models suggest that litter size after cross-fostering at the start of lactation influences the predicted degree of sow BW change, and increased sow ADFI will improve, or minimize, BW change during lactation. Within the BCAA, the models indicate that increasing dietary Leu:Lys will minimize sow BW change during lactation. Lastly, the optimum equation for sow ADFI included Leu:Trp, SID Lys, NE, CP, and Leu:Lys as significant predictive variables. The model indicates that reducing Leu:Trp and increasing Leu:Lys will positively impact sow feed intake during lactation. Overall, the prediction equations suggest that BCAA play an important role in litter growth, sow BW change, and feed intake during lactation; however, the influence of BCAA on these criteria is much smaller than that of other dietary components such as NE, SID Lys, sow ADFI, and CP. These responses suggest that the three BCAA are essential for lactating sow and litter growth performance, but the predicted influence of Leu, Ile, and Val differ among litter ADG, sow weight loss, and sow daily feed intake.
Keywords: branched-chain amino acids; lactation; litter performance; sow